Konsep Perwakilan Fungsional Utusan Golongan Dalam Sistem Perwakilan Di Indonesia - Rizki Agus Saputra (LPPM Universitas Ekasakti Padang, 2024)
The aim of the research is to provide an understanding of the urgency of re-implementing the concept of functional representation in the Indonesian parliament. The emergence of the concept of functional representation or the principle of functional or occupation representation needs to be paid attention to and its importance recognized wherever possible, in addition to the political representation system, as a way to incorporate expertise or expertise into the decision-making process that concerns the public interest.. In Indonesia, the principle of functional representation has also been known, in addition to the principle of political representation. The Karya Group (Golkar), which was based on the principle of functional representation, then shifted to political representation, like other political parties. With the various descriptions of the representative system mentioned above, it can be seen that apart from political representation which is considered reasonable, functional representation also needs to be considered and recognized for its importance as a way to include economic elements and other group elements (group representatives) in the political process in the Indonesian parliament.